2019
DOI: 10.1002/1873-3468.13439
|View full text |Cite
|
Sign up to set email alerts
|

Protective Dps–DNA co‐crystallization in stressed cells: an in vitro structural study by small‐angle X‐ray scattering and cryo‐electron tomography

Abstract: Under severe or prolonged stress, bacteria produce a nonspecific DNA‐binding protein (Dps), which effectively protects DNA against damaging agents both in vitro and in vivo by forming intracellular biocrystals. The phenomenon of protective crystallization of DNA in living cells has been intensively investigated during the last two decades; however, the results of studies are somewhat contradictory, and up to now, there has been no direct determination of a Dps–DNA crystal structure. Here, we report the in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 39 publications
10
40
0
Order By: Relevance
“…It was also demonstrated that Dps is unable to bind DNA directly and Dps-DNA complex formation relies on the ion bridges formed by Mg 2+ [32,33]. However, our recent results demonstrate a formation of highly ordered Dps-DNA complexes in solution in the absence of the metal ions [9].…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…It was also demonstrated that Dps is unable to bind DNA directly and Dps-DNA complex formation relies on the ion bridges formed by Mg 2+ [32,33]. However, our recent results demonstrate a formation of highly ordered Dps-DNA complexes in solution in the absence of the metal ions [9].…”
Section: Introductionmentioning
confidence: 62%
“…It is well-known that histones being basic protein components of chromatin act as spools around which DNA winds. In our previous work, we proposed a Dps-DNA binding model based on the SAXS data where DNA is bent around Dps confirming histone-like nature of the protein [9]. Dps proteins have been found in the majority of bacterial groups, including archaea [10].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…This technique has achieved subnanometer reconstructions of pleomorphic viruses with imperfect helical symmetry and could prove similarly useful for solving structures from tomograms of disordered nanocrystals [71]. In addition to extending the high-resolution limit of structure determination, the ability to spatially characterize disorder could provide insights into both the organization of proteins that form ordered arrays in vivo and defects in these biological crystals [72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…The observation of crystals in living cells, reported in the literature as in cellulo or in vivo crystals is known for decades and was repeatedly described as a natural phenomenon . Examples are crystals of storage proteins in seeds, insulin crystals within secretory granules, solid state catalysts, biocrystallization of the DNA‐binding protein (Dps) and DNA as a response to cellular damage and stress, or β‐hematin crystals produced as a detoxification strategy by malaria parasites . Although in cellulo crystallization still is a new exciting area in cell biology, many natively crystallizing proteins in living cells first function as storage such as vitellin yolk protein crystals from bullfrog oocytes, from leopard frogs, from A. aegypti oocytes, lipovitellin from bony fish oocytes, edestin from hemp plant, tobacco seed protein and Cry protein in B. thuringiensis , trichocyst matrix protein in Paramecium and food milk protein in Diplotera punctata .…”
Section: Introductionmentioning
confidence: 99%